Nutrition, a health technology that deserves increasing interest among HTA doers. A systematic review - Gutiérrez-Ibarluzea, Iñaki; Arana-Arri, Eunate (Frontiers in Pharmacology, 2015)
The increasing interest for evaluating indirect consequences of health care interventions and their interaction with patients’ behavior have put the focus on health promotion interventions including nutrition and the need to measure and evaluate them. Objective: In this review we have aimed to analyze current status of written and published reports on nutrition and nutrition interventions by HTA doers, how assessment has been approached and which metrics and designs have been proposed. Methods: For that purpose, we searched the Centre for Reviews and Dissemination databases (CRD) comprising the International Network of Agencies for HTA database (INAHTA), the database of effects (DARE) and the National Health Service Economic Evaluation Database (NHS EED). The words used include nutrition and nutrition interventions and there was no limit on data coverage. We complemented the search by manually seek for further reports on INAHTA’s agencies webpages. We extracted the reports for their classification and analysis. Results: We found 82 reports and after applying inclusion and exclusion criteria, we finally included 42. All the reports correspond to High income Countries (HiC) including agencies from Europe, North America and Oceania. The agencies or programs most represented correspond to the NIHR (UK) and AHRQ (USA). There were general reports around the role of functional foods and specific reports on the impact of establishing nutrition specific strategies in hospitals. 6 out of 42 analyzed the economic consequences of nutrition interventions and 4 reports were related to the methodologies used or the appliance of systematic review methods to the field of nutrition. Conclusions: Retrieved reports confirm the use and utility of systematic reviews and economic analysis and their applicability for nutrition interventions. However, some measurements such as Quality Adjusted Life Years (QALY) need to be refine to better reflect the impact of these interventions.